Computational Numerical Solution Algorithm for Fractional Differential Equations - Bawa’neh, Sameer Hassan Saleeh (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
This study focused on three main problems, firstly, a study on the existence of the solution for a coupled system of fractional differential equations with integral boundary conditions. The solution process for the existence and uniqueness of solutions for the proposed problem was obtained by using the contraction mapping principle, and then by using Leray–Schauder’s alternative method. Secondly, investigation and approximation of solutions of Caputo type fractional differential equation with nonlinear boundary conditions has been solved by using an appropriate parameterization technique, where nonlinear boundary conditions were transformed to linear boundary conditions by using vector parameters. To solve the transformed problem, a numerical-analytic scheme was constructed to find the relation between different type’s two-point and multipoint linear boundary condition and nonlinear boundary conditions. Finally, efficient numerical - analytical computational algorithm for solving systems of fractional differential equations (SFDEs) Nonlinear Point Boundary-Value Problem with Nonlinear Boundary Conditions were considered. The fractional derivative was described in the Caputo sense. The method is based on numerical approximations of systems of fractional differential equations, where the properties of this method were utilized to reduce SFDEs to the system of algebraic equations. Special attention is given to study the convergence and estimate the error of the presented method. The methods introduce a promising tool for solving many systems of non-linear fractional differential equations. Numerical examples were presented to illustrate the validity and the great potential of both proposed techniques.

ÖZ: Bu çalışma, üç temel probleme odaklanmış, ilk olarak, integral sınır koşulları olan birleştirilmiş kesirli diferansiyel denklem sistemi için çözümün varlığına ilişkin bir çalışma. Önerilen problem için çözümlerin varlığı ve tekliği için çözüm süreci, büzülen dönüşüm özelliğini kullanarak ve sonra Leray-Schauder’in alternatif yöntemini kullanarak elde edildi. İkincisi, Caputo tipi kesirli diferansiyel denklemin çözümlerinin doğrusal olmayan sınır koşullarıyla araştırılması ve yakınlaştırılması, doğrusal olmayan sınır koşullarının vektör parametreleri kullanılarak doğrusal sınır koşullarına dönüştürüldüğü uygun bir parametre belirleme tekniği kullanılarak çözülmüştür. Dönüştürülen problemi çözmek için, farklı türün iki noktalı ve çok noktalı doğrusal sınır koşulu ile doğrusal olmayan sınır şartları arasındaki ilişkiyi bulmak için sayısal-analitik bir şema oluşturulmuştur. Son olarak, kesirli diferensiyel denklem sistemlerinin çözümü için etkin sayısal - analitik hesaplama algoritması, Lineer Olmayan Sınır Koşulları ile Lineer Olmayan Nokta Sınır Değer Problemi ele alınmıştır. Yöntem, kesirli diferensiyel denklem sistemleri cebirsel denklem sistemine indirgemek için bu yöntemin özelliklerinin kullanıldığı kesirli diferansiyel denklem sistemlerinin sayısal yaklaşımlarına dayanmaktadır. Yakınsama çalışmalarına ve sunulan yöntemin hatasını tahmin etmeye özel önem verilir. Yöntemler, birçok doğrusal olmayan kesirli diferensiyel denklem sistemini çözmek için umut verici bir araç sunmaktadır. Her iki önerilen tekniğin geçerliliğini ve yüksek potansiyelini göstermek için sayısal örnekler sunulmuştur.
Doctor of Philosophy in Mathematics. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Mathematics, 2019. Supervisor: Prof. Dr. Nazim Mahmudov.
Keywords: Mathematics; Applied Mathematics and Computer Science; Differential Equations; Fractional differential equation; sequential; Caputo; nonlocal integral boundary conditions